Banning Ideologies in EFL Classrooms: A Critical Discourse Analysis of Teachers’ Pedagogical Talk - Yenni Hasnah; Pirman Ginting (JADEs Journal of Academia in English Education, 2026)
Classroom discourse is no longer perceived as a neutral conduit for knowledge dissemination but rather as a locus of ideological negotiation, regulation, and control. Accordingly, educational environments are inherently normative spaces where certain actions and attitudes are intentionally discouraged to maintain institutional order and instructional effectiveness. Therefore, this study examines the phenomenon of ideological banning in classroom discourse through the application of critical discourse analysis. Drawing on qualitative data from two teachers’ pedagogical discourse, this study reveals four major prohibited ideologies involving academic dishonesty, passivity, fixed mindset, and lack of personal responsibility. Using Fairclough’s three-dimensional model for analyzing the data, the study demonstrates that instructors deploy a range of linguistic mechanisms, including imperatives, direct language, casual language, conditional clauses, humor, and directives to establish ideological boundaries. These tactics operate not merely to govern classroom conduct but also to mold students’ cognitive, ethical, and emotional growth. The findings contribute to applied linguistics by defining ideological banning as a novel analytical construct and offering empirical insights into teacher discourse as a mechanism of epistemic and ideological control. Thus, educational discourse not only reflects but also preserves and negotiates prevalent society ideals, thereby contributing to broad discourses around language, power, and education.